2019
DOI: 10.1002/jcsm.12432
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a multimodal intervention in functionally impaired older people with type 2 diabetes mellitus

Abstract: Background Type 2 diabetes, a highly prevalent chronic disease, is associated with increasing frailty and functional decline in older people. We aimed to evaluate the effectiveness of a multimodal intervention on functional performance in frail and pre‐frail participants aged ≥70 years with type 2 diabetes mellitus. Methods The MID‐Frail study was a cluster‐randomized multicenter clinical trial conducted in 74 trial sites across seven European countries. The trial recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
90
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(104 citation statements)
references
References 42 publications
9
90
0
5
Order By: Relevance
“…6-13 18 27 43-45 Usual walking speed, timed chair stand speed, grip strength, and standing balance inclusive of scoring SPPB are likely to be useful not only for evaluating the cross-sectional status but also for promoting physical activity intervention by monitoring the changes in the levels. [43][44][45][46] Most of the studies dealing with physical performance measures examined individuals without diabetes, and only a few studies were done involving patients with diabetes. 13 45 These measures must be incorporated into daily practice for patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…6-13 18 27 43-45 Usual walking speed, timed chair stand speed, grip strength, and standing balance inclusive of scoring SPPB are likely to be useful not only for evaluating the cross-sectional status but also for promoting physical activity intervention by monitoring the changes in the levels. [43][44][45][46] Most of the studies dealing with physical performance measures examined individuals without diabetes, and only a few studies were done involving patients with diabetes. 13 45 These measures must be incorporated into daily practice for patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…MetaboFrail was developed as an ancillary study of the "Multi-modal Intervention in Diabetes in Frailty" (MID-Frail) project [16,33,34]. The latter was a cluster-randomized multicenter clinical trial that evaluated the effectiveness of a multicomponent intervention (mainly based on resistance exercise and lifestyle counseling) on improving physical performance compared with usual care in F-T2DM older adults from seven European countries (ClinicalTrials.gov identifier: NCT01654341) [16,33].…”
Section: Study Populationmentioning
confidence: 99%
“…A recent meta-analysis of 31 studies including 4794 participants concluded that resistance exercise, with or without nutrition supplementation may improve the frailty status of older adults in primary care settings. In older subjects with diabetes and frailty, resistance exercise as part of a multimodal approach significantly improved physical performance over one year measured by the short performance physical battery (SPPB) which was accompanied by a significant decrease in healthcare expenditure ( 59 ). Comprehensive Geriatric Assessment was also more effective than control groups at reducing frailty ( 58 ).…”
Section: Management Of Frailtymentioning
confidence: 99%